Effects of a modular telehealth intervention on comorbid conditions in service members with mild traumatic brain injury - Jesse R. Fann; Jesse R. Fann; Tessa Hart; Kathleen R. Bell; Wesley Cole; Sonia Jain; Rema Raman; Jason Barber; Sureyya Dikmen; Sureyya Dikmen; John Richardson; Murray B. Stein; et al. (Frontiers in Neurology)
ObjectiveMany active duty service members with mild traumatic brain injury (mTBI) report comorbidities such as depression, anxiety, PTSD, insomnia, and pain. We analyzed data from a prior randomized controlled trial (RCT) to examine the effects of evidence-based treatment modules, delivered by telephone, on the number and symptom burden of five common comorbidities.Setting and participants356 service members from two military medical centers who had sustained deployment-related mTBI in the preceding 2 years.DesignSecondary analysis of RCT comparing 6 months of telephone-delivered problem-solving treatment (PST) with comorbidity-specific modules to education only (EO).Main measuresComorbidity burden measured by Patient Health Questionnaire-9, Brief Symptom Inventory-Anxiety, PTSD Checklist, Pittsburgh Sleep Quality Inventory, Rivermead Postconcussion Symptoms Questionnaire (headache item) assessed at baseline and 6 and 12 months.Results47% of service members endorsed ≥ 3 comorbidities at baseline. At 6 months, the PST group had significantly fewer comorbidities, greater improvement in depression, anxiety, PTSD, and sleep, but not headache, and higher response/remission rates for depression and sleep, compared to EO. There were no significant group differences at 12 months.ConclusionTelephone-delivered PST with comorbidity-specific modules reduces burden of comorbidities after deployment-related mTBI. Research is needed on how to maintain improvements over time.